2020
DOI: 10.1089/dia.2020.0085
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Dexcom G6 Continuous Glucose Monitoring System in Pregnant Women with Diabetes

Abstract: Background: The aim of this study was to determine the performance of the Dexcom G6 continuous glucose monitoring (CGM) system across three sensor wear sites in pregnant women with diabetes in the second or third trimesters. Methods: Participants with type 1 (T1D), type 2 (T2D), or gestational (GDM) diabetes mellitus were enrolled at 3 sites. Each wore two G6 sensors on the abdomen, upper buttock, and/or posterior upper arm for 10 days and underwent a six-hour clinic session between days 3 and 7 of sensor wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 37 publications
2
34
1
1
Order By: Relevance
“…With mean ARD ranging from 11.2 to 15.9% during aerobic, resistance and HIIT exercises, this study observed somewhat reduced numeric accuracy compared to recent at-rest results of the G6 system in pregnant women with diabetes for example (mean ARD 8.7–11.5%) [ 33 ]. Many variables may impact the readings of interstitial glucose during exercise and describing these as errors in accuracy is in part misleading.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…With mean ARD ranging from 11.2 to 15.9% during aerobic, resistance and HIIT exercises, this study observed somewhat reduced numeric accuracy compared to recent at-rest results of the G6 system in pregnant women with diabetes for example (mean ARD 8.7–11.5%) [ 33 ]. Many variables may impact the readings of interstitial glucose during exercise and describing these as errors in accuracy is in part misleading.…”
Section: Discussioncontrasting
confidence: 69%
“…As CGM devices continue to evolve and improve their accuracy, additional studies are required to characterize how well they perform during exercise. Although the general accuracy of the latest factory-calibrated Dexcom G6 system has been examined [ 32 , 33 ], no study has yet assessed the impact that exercise has on the accuracy of this sensor.…”
Section: Introductionmentioning
confidence: 99%
“…It is accurate enough to replace self-monitoring of blood glucose (SMBG) for precise prandial insulin dosing in type 1 diabetes pregnancy and is also CE marked for use during pregnancies complicated by type 1 diabetes, type 2 diabetes, and gestational diabetes. 2 The Dexcom G6 further benefits from its interoperability, meaning that it can be used either as a standalone real-time CGM system for those using insulin pumps or multiple daily injections or together with a subcutaneous insulin pump (currently a DANA pump in Europe or Tandem T-slim pump in North America) as part of an automated insulin delivery system. As evidence supporting the use of CGM in pregnancy continues to build, it is important to understand how CGM can be leveraged to improve pregnancy outcomes as well as to better characterize the relationship between maternal glycemia and diabetes-related complications in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The Dexcom G6 is a game changer in terms of a real-time CGM with hypoglycemia alerts and alarms. It is accurate enough to replace self-monitoring of blood glucose (SMBG) for precise prandial insulin dosing in type 1 diabetes pregnancy and is also CE marked for use during pregnancies complicated by type 1 diabetes, type 2 diabetes and gestational diabetes 2 . The Dexcom G6 further benefits from its interoperability meaning that it can be used either as a standalone real-time CGM system for those using insulin pumps or multiple daily injections or together with a subcutaneous insulin pump (currently a DANA pump in Europe or Tandem T-slim pump in North America) as part of an automated insulin delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…This system allows for frequent sampling of calculated glucose levels without the need for repetitive fingerstick testing by glucometer. The Dexcom G6 CGM system (Dexcom Inc., San Diego, CA, USA) is one of two FDA-approved systems to replace fingerstick glucose monitoring without requiring the entry of glucometer values for calibration [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Both the FreeStyle Libre and Dexcom G6 system have similar reported accuracies, however the FreeStyle Libre was not approved for use in children at the initiation of this study [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%